ChatGPT & Other Generative AI Tools as University Teaching Aids - Stuart Hargreaves (Legal Education Review)
This paper describes experimentation with various generative AI tools in the delivery of a large lecture course at a law school between September and December 2023. Three techniques were adopted – AI-generated lecture summaries, AI-generated quizzes used in a ‘low-stakes’ setting, and a course chatbot. The paper explains the process used to employ each of these and reviews student surveys as to their effectiveness. It argues that the experiment shows that AI tools can be deployed at low cost and can be very effective in allowing course instructors to add forms of informal, formative assessment where a lack of resources might otherwise make that prohibitive.